STUDI KASUS: ASUHAN KEBIDANAN PADA BAYI BARU LAHIR DENGAN CAPUT SUCCEDANEUM - Laorina Regel (Poltekkes Kemenkes Maluku, 2022)
Caput Succedaneum is a birth scar that is seen in the head area sometime after the baby is born, this is due to the strong pressure on the head area when entering the birth canal resulting in damming of the peripheral circulatory and lymph which is accompanied by discharge of body fluids into the extravascular tissue which causes oedemas or lumps in the baby's head area, this abnormality is found during prolonged labor or by vacuum extraction, conditions that occur in newborns often cause concern for the family about the baby's condition, in some families the caput succedaneum can pose a danger to the baby because the lump is located in the head area, This case study describes a newborn girl, full term, with a lump in the left side of the head, the family is very anxious, worried about the condition of her baby. Efforts to deal with concerns in the family are provided by counseling and health education for the family and handling the caput in infants, providing adequate breastfeeding, keeping the baby warm, not picking the baby up, avoiding wearing hats, giving stimulation to the caput area slowly for 5-10 minutes to stimulate lymph vessels to absorb fluid. Comprehensive and ongoing support and assistance from health workers to obtain maximum care results, the results of care carried out by caput succedaneum disappear the second day, family anxiety is no longer there, there is family understanding about the condition of the baby, educational suggestions for caput care Involving the family is very effective for healing.